The Impact of the COVID-19 Pandemic on The Profitability of Business Entities Operating in The Horeca Industry in Poland in 2020 Based on Financial Statements - Sabina ROKITA (Communications of International Proceedings, 2021)
More than 1.5 years after the appearance of the SARS-CoV-2 coronavirus and the COVID-19 pandemic it has caused almost everywhere in the world, it can be concluded that the economic impact of these events has been devastating, despite the fact that they have at times contributed to the significant development of some industries. The article discusses the impact of the COVID-19 pandemic on the profitability of business entities operating in the HoReCa industry (Hotel, Restaurant, Catering/Cafe) in Poland in 2020, based on financial statements. The study covered a group of 827 business entities, including 396 operating in the area of accommodation and 431 operating in the area of catering.
Keywords: Horeca Industry; COVID-19 Pandemic; Financial Statements